PROGRAM BASIC UNTUK PENENTUAN BATAS ELASTIS KEKUATAN LENTUR STATIS - Suparman Kamasudirdja (Jurnal Penelitian Hasil Hutan, 1988)
One of  the procedures  for  determining the elastic  limit  in static  bending  test  is through  eye  fitting  of  a  successive load-deflection   reading  with  a  straight  line  on  a  graph paper.   The  procedure   is simple  and  does  not  require  elaborate apparatus. Consequently, it  is still  applied  in  many  testing  laboratories.  The  above  procedure   however, contains  some weakness,   namely  it  is laborious,  time  consuming,  subjective   and  is  inconsistent   within   the same  and among  different plotters.An  attempt  was made  by  the author  to use cheap personal pocket   computer  for finding  the elastic limit of load and deflection,   and  hence  also  the  corresponding   modulus  of  elasticity  and  bending- strength  within  elastic  limit.  The  basic programme   prepared  by  the author,  whenever  needed  can be used also for  converting  the observed  load/deflection data into  calibrated  values or other  measurement  units.  This could  be done for example  after data checking,  or debugging step by  inserting a jump  command  to a specific  sub-routine   which  will handle specific  computation